Serum leptin levels, skin leptin and leptin receptor expression in psoriasis - ERGUN, SAFİYE ATLAS TÜLİN; BOZKURT, SÜHEYLA (WILEY, 2008)
Background Recent studies support the relation of psoriasis with obesity and cardiovascular disease. Leptin, a peptide hormone secreted predominantly from adipose tissue, is involved in the regulation of energy intake and expenditure. Recently, it has been shown to have several immunological effects including induction of proinflammatory cytokine production. Objectives To investigate the possible role of leptin in psoriasis pathogenesis. Methods Forty-three patients with psoriasis, 10 diseased and 10 healthy controls with normal body mass index were included. Serum fasting leptin levels of the study group were examined by enzyme-linked immunosorbent assay. Tissue leptin and leptin receptor expression of both patients and controls were investigated by immunohistochemistry. Results Serum leptin levels, tissue leptin and leptin receptor expression were significantly higher in patients with severe psoriasis than patients with mild-moderate psoriasis and controls (P < 0.05). Serum leptin levels showed a positive correlation with Psoriasis Area and Severity Index and involved body surface area in patients with psoriasis. In addition, serum leptin levels, tissue leptin and leptin receptor expression showed a positive correlation with disease duration in patients with psoriasis (P < 0.01, r = 0.979; P < 0.01, r = 0.691; P < 0.01, r = 0.428, respectively). Conclusions We assume that leptin might serve as a marker of severity in psoriasis and also may be a pathogenetic cofactor contributing to chronicity of the disease. Consequently, its role in obesity and cardiovascular disease in patients with psoriasis deserves to be studied. In addition, drugs targeting the proinflammatory effects of leptin may be a new adjuvant therapeutic approach in psoriasis.
Keywords: leptin; leptin receptor; psoriasis; Psoriasis Area and Severity Index; IMMUNE-RESPONSE; RISK; INFLAMMATION; SMOKING; OBESITY; DISEASE